Letterkenny. Season 2 [videorecording (DVD)] - Tierney, Jacob, 1979-; Keeso, Jared; Dales, Nathan; Mylett, Michelle, 1989- (Universal Studios Home Entertainment, 2019)
The residents of Letterkenny belong to one of three groups: the hicks, the skids, and the hockey players, who are constantly feuding with each other over seemingly trivial matters that often end with someone getting their ass kicked.